Ostrich eggshell as an onlay bone-graft substitute for orbital blow-out fractures - Rhoumel A. Yadao, MD; Gloria D. Lim, MD; Lawrence C. Pe,MD; Allan M. Valdez, MD; Susan Cristobal, MD; Alice Tuesday C. Sunico, MD; Hazel L. Romero, MD (Philippine Journal of Ophthalmology)
Objective: To assess the biological behavior of an ostrich eggshell implant as an onlay graft on the orbital floor.